Modernization of Ultrasonic Inspection of RBMK-1000 Reactor Zirconium Channels - A. G. Rodygin; R. V. Pirozhkov; E. A. Tsvelik (Глобальная ядерная безопасность)
The paper considers the modernization of the SK-26 ultrasonic control machine used for monitoring welded joints of zirconium channels in the nuclear power industry. Proposed changes in the design of the machine and positioning system of the machine on the plateau will lead to a significant reduction in treatment time control and greater operator safety during operation.